Post mortem findings and bacterial characterization of equine salmonella septicemia. A case report - Segura, Enid (2022)
The first duly confirmed case of equine salmonellosis in Costa Rica is described, a seven-month-old Ibero-American filly with a four-week-long case of diarrhea and poor body condition. The presence of Salmonella enterica subspecies enterica was confirmed through a bacteriological study of stool samples. In the post-mortem study, severe extensive ulcerative and necrotizing typhlocolitis was observed.